2017
DOI: 10.1186/s12933-017-0623-6
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone stabilizes atherosclerotic plaque by regulating the Th17/Treg balance in AMPK-dependent mechanisms

Abstract: BackgroundPioglitazone (PIO), a thiazolidinediones drug, is a well-known anti-diabetic medicine, but its anti-atherosclerotic effects remain controversial. Thus it is important to investigate the effects of PIO on atherogenesis and the relevant mechanisms.MethodsFor in vitro studies, primary cultured or AMP-activated protein kinase (AMPK) inhibited splenocytes were treated with oxidized low density lipoprotein (ox-LDL) or ox-LDL plus PIO. Percentage of T helper 17 (Th17) and regulatory T (Treg) cells were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 42 publications
(45 reference statements)
1
29
0
Order By: Relevance
“…Previous studies demonstrated that statin and anti-diabetic therapies may decrease the rate of coronary plaque progression and may participate in plaque stabilization (7)(8)(9). Previous experiments performed in our laboratory have shown that the use of aged garlic extract (AGE) is associated with a significant reduction in low attenuation plaque (LAP) progression as compared to the placebo using CCTA in patients with metabolic syndrome (10).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that statin and anti-diabetic therapies may decrease the rate of coronary plaque progression and may participate in plaque stabilization (7)(8)(9). Previous experiments performed in our laboratory have shown that the use of aged garlic extract (AGE) is associated with a significant reduction in low attenuation plaque (LAP) progression as compared to the placebo using CCTA in patients with metabolic syndrome (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although prospective randomized controlled trials (RCTs) have provided cardiovascular safety data on various ADAs including sulphonylureas (SU) [ 7 ], thiazolidinediones (TZD) [ 8 10 ], alpha-glucosidase inhibitors (AGI) [ 11 , 12 ], and dipeptidyl peptidase-4 inhibitors (DPP-4I) [ 13 15 ], these trials were not designed to compare the individual ADAs as the add-on medication to baseline metformin monotherapy [ 16 ]. A landmark RCT comparing cardiovascular outcomes of SU, DPP-4I, glucagon-like peptide-1 analogues and insulin as second-line agents to metformin in newly diagnose T2DM patients is expected to be completed in 2020 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the proportions of circulating Tregs in AITDs tended to be lower than those in HCs [11][12][13][14][15][16][17][18][19][20][21][22], while others reported the opposite result [23,24]. Considering that drugs including methimazole [25] might affect the differentiation and proliferation of Tregs through regulation of AMP-activated protein kinase (AMPK) [26] and signal transducer and activator of transcription 3 (STAT3) [27], we speculated that the origins of these differences between results lie in differences in the treatment statuses of the AITDs involved in the studies. Therefore, we performed a meta-analysis of the proportions of peripheral blood Tregs among CD4+ T cells of untreated and treated AITDs to explore how Tregs function in the pathogenesis of AITD.…”
mentioning
confidence: 99%